2016
DOI: 10.1016/j.jsp.2016.07.002
|View full text |Cite
|
Sign up to set email alerts
|

A cluster randomized controlled trial of the Promoting Alternative Thinking Strategies (PATHS) curriculum

Abstract: This randomized controlled trial (RCT) evaluated the efficacy of the Promoting Alternative Thinking Strategies curriculum (PATHS; Kusche & Greenberg, 1994) as a means to improve children's social–emotional competence (assessed via the Social Skills Improvement System (SSIS); Gresham & Elliot, 2008) and mental health outcomes (assessed via the Strengths and Difficulties Questionnaire (SDQ); Goodman, 1997). Forty-five schools in Greater Manchester, England, were randomly assigned to treatment and control groups.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 55 publications
2
48
0
4
Order By: Relevance
“…Numerous randomised controlled trials (RCTs) have consistently established small-to-moderate effects on a range of outcomes, including children's social and emotional skills, externalising problems (e.g. aggressive behaviour) and academic attainment [15][16][17][18][19][20][21][22][23][24][25]. However, many trials finding positive effects of PATHS have involved or been led by the developer.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous randomised controlled trials (RCTs) have consistently established small-to-moderate effects on a range of outcomes, including children's social and emotional skills, externalising problems (e.g. aggressive behaviour) and academic attainment [15][16][17][18][19][20][21][22][23][24][25]. However, many trials finding positive effects of PATHS have involved or been led by the developer.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, social and emotional learning programmes have been mostly delivered by teachers in schools and evaluated by large‐scale studies (Durlak et al, ; Durlak, Weissberg, & Pachan, ; Durlak, Weissberg, Dymnicki, Taylor, & Schellinger, ; Humphrey, ). Nevertheless, the lack of an appropriate and rigorous implementation and evaluation makes the application of such initiatives in other contexts difficult (Pérez‐González, , ; Humphrey et al, ). Despite research growing in this area, more studies are needed to identify their feasibility and acceptability (Lendrum & Wigelsworth, ).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the lack of an appropriate and rigorous implementation and evaluation makes the application of such initiatives in other contexts difficult (Pérez-González, 2008, 2015Humphrey et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Through PATHS, students practice and apply how to identify and describe a wide range of feelings, calm themselves through breathing techniques, and take others' perspectives to solve problems (Weissberg & O'Brien, 2004). In a study researched by Humphrey et al (2016), after implementing PATHS for a two-year process in two elementary aged focus groups, there was a significant increase in teachers' perceptions of change in student's social-emotional competence and pro-social behavior, and there was a decrease in emotional symptoms and conduct problems. This study indicates that PATHS benefits emotional competence in students; though it might be a slower process, due to it only being implemented in the classroom.…”
Section: Sel Program Strategies and Interventionsmentioning
confidence: 99%
“…Many previous studies regarding the two SEL studies, PATHS and The Zones of Regulations, indicated that the inclusion of these programs benefit emotional competence and self-regulation behaviors in students with ID (Humphrey at al., 2016;Kuypers, 2011). The combined SEL programs highlighted the main points of each program that would best benefit the students in this study.…”
Section: Ch 5: Implicationsmentioning
confidence: 99%